Diagnosis and treatment of diabetic retinopathy and diabetic macular edema: clinical practice guidelines of the Peruvian Health Social Security (EsSalud) - Cáceres-del-Carpio, Javier Héctor (2020)
Introduction. This article summarizes the clinical practice guidelines (CPG) for the diagnosis and treatment of diabetic retinopathy and diabetic macular edema of the Health Social Security of Peru (EsSalud). Objective. To provide clinical recommendations based on evidence for the diagnosis and treatment of diabetic retinopathy and diabetic macular edema in EsSalud. Methods. A guidelines elaborating group (GEG) was conformed by medical specialists and methodologists. The GEG formulated 4 clinical questions intended to be answered by this CPG. For each of these questions systematic searches of systematic reviews and primary studies (when considered pertinent) were carried out in PubMed during 2018. Evidence was selected in order to reply each of the proposed clinical questions. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. During periodic working meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice and the management flowchart. Results. The present CPG addressed 4 clinical questions of four topics: screening, diagnosis, treatment of choice and adjuvant treatment. Based on these questions, 6 recommendations (4 strong and 2 conditional), 19 points of good clinical practice, and 1 management flowchart were formulated. Conclusion. This article summarizes the methodology and conclusions based on evidence from the CPG for the diagnosis and treatment of diabetic retinopathy and diabetic macular edema in EsSalud.